ERS Presidential Summit 2018: multimorbidities and the ageing population. Issue 3 (25th September 2019) - Gaga, Mina; Powell, Pippa; Almagro, Marta; Tsiligianni, Ioanna; Loukides, Stelios; Roca, Josep; Cullen, Matthew; Simonds, Anita K.; Ward, Brian; Saraiva, Isabel; Troosters, Thierry; Robalo Cordeiro, Carlos
As the average age of the population increases, so will the prevalence of chronic respiratory diseases and associated multimorbidity. This will result in a more complex clinical environment. Part of the solution will be to allow patients to be co-creators in the design of their care. It will also require clinicians to shift in their current approaches to care, step out of the disease- or pathology-oriented approach and embrace new ideas. In an effort to prepare the respiratory community for the challenge, we reflect on concepts to empower patients via multidisciplinary systems, new technologies and transition from end-of-life care to advanced care planning. Increasing life expectancy will lead to the need for better respiratory and multimorbid care http://bit.ly/2KgLvGu